An essay on the power discourse of rights: The history, politics and end of human rights - Nuncio, Rhoderick V. (Animo Repository, 2005)
The article prefigures the constraining yet enabling discourse on and practice of human rights. It asks the question whether a certain thematic discourse exists and, if ever there is such discourse, whether it reflects human nature and the nature of human rights. The assumption runs contrary to other claims made by political and social philosophers. In modifying farther the critical stance of this paper, the history of human rights is discussed. It shows how the theory of political and human rights precedes its actual praxis and its essential nature. Yet, if ever a thematic discourse is present, the paper proposes the idea of power. Equality of men is contrary to power exercised by people, by institutions, and by the State. The dissolution of this power is the end of human rights.